Oral health in adolescents with disabilities from centro de educación especial San Miguel, Guarambaré, Paraguay - Pérez-Bejarano, Nohelia María; Ferreira-Gaona, Marta Inés; Díaz-Reissner, Clarisse Virginia; Sanabria-Vázquez, Diana Alicia; Torres-Amarilla, Carlos Daniel; Acosta-Parra, Eliana Belén; Portillo-Martínez, María Alejandra; Rojas-Orrego, Verónica Mariela; Samaniego-Valdez, Ana Belén; Sian, Gilda Guadalupe (Revista Facultad de Odontología Universidad de Antioquia, 2017)
Introduction: oral health in patients with disabilities represents a great challenge in dentistry, as motor, sensory, cognitive, behavioral, and emotional limitations influence oral hygiene, leading to the development of certain diseases in this population. The aim of the present study was to analyze the oral health conditions of school children with disabilities aged 12 to 18 years attending Centro de Educación Especial San Miguel, in the city of Guarambaré, in 2013. Methods: this was a descriptive cross-sectional study. A survey was applied to 20 schoolchildren who met the inclusion criteria. Oral health was assessed using the DMFT index, as well as the dental plaque, tartar, gingival indices and occlusal anomalies. Results: the DMFT index was 5.5 (SD = 4.38), dental plaque index was 1.15, tartar was 0.53 and gingival index was 0.68. There was malocclusion in 50% of cases, of which 35% were class II and 15% class III. Conclusions: the school children participating in this study do not enjoy good health conditions because of the high rate of tooth decay, high percentages of dental plaque, and a large percentage of preventive and restorative needs.